Correlation of Serum and Ascitic Fluid Soluble Form Urokinase Plasminogen Activator Receptor Levels With Patient Complications, Disease Severity, Inflammatory Markers, and Prognosis in Patients With Severe Acute Pancreatitis. Issue 3 (March 2019) - Long, Ding; Wang, Yujun; Wang, Hui; Wu, Xiaoling; Yu, Li
Abstract : Objectives: The aim of the study was to investigate the correlation of serum and ascitic fluid soluble form urokinase plasminogen activator receptor (suPAR) levels with patients' complications, disease severity, inflammatory markers, and prognosis in patients with severe acute pancreatitis (SAP). Methods: Fifty patients with SAP, 47 patients with mild acute pancreatitis, and 50 healthy controls were enrolled. Serum samples were obtained from all participants after enrollment; meanwhile, ascitic fluid samples were collected from 20 patients with SAP who developed ascites. Serum and ascitic fluid suPAR levels were determined by enzyme-linked immunosorbent assay. Results: Serum suPAR level was greatly elevated in patients with SAP than patients with mild acute pancreatitis and healthy controls. Receiver operating characteristic curve showed that serum suPAR presented with good value in predicting risk of pancreatic necrosis, pancreatic infection, and multiple organ dysfunction syndrome, whereas serum suPAR did not predict mortality. Serum suPAR level was also positively correlated with Acute Physiology and Chronic Health Evaluation II score, Balthazar index, and Sequential Organ Failure Assessment score. As to ascitic fluid suPAR, it was positively correlated with serum suPAR level, Acute Physiology and Chronic Health Evaluation II score, Sequential Organ Failure Assessment score, risk of pancreatic infection, and multiple organ dysfunction syndrome. Conclusions: Serum and ascetic fluid suPAR levels could be served as markers for disease severity and risk of severe complications in patients with SAP. Abstract : Supplemental digital content is available in the text.